Solid-State Order and Charge Mobility in [5]- to [12]Cycloparaphenylenes - YAVUZ, İLHAN (AMER CHEMICAL SOC, 2019)
We report a computational study of mesoscale morphology and charge-transport properties of radially pi-conjugated cycloparaphenylenes ([n]CPPs) of various ring sizes (n = 5-12, where n is the number of repeating phenyl units). These molecules are considered structural constituents of fullerenes and carbon nanotubes. [n]CPP molecules are nested in a unique fashion in the solid state. Molecular dynamics simulations show that while intramolecular structural stability (order) increases with system size, intermolecular structural stability decreases. Density functional calculations reveal that reorganization energy, an important parameter in charge transfer, decreases as n is increased. Intermolecular charge-transfer electronic couplings in the solid state are relatively weak (due to curved 2r-conjugation and loose intermolecular contacts) and are on the same order of magnitude (similar to 10 meV) for each system. Intrinsic charge-carrier mobilities were simulated from kinetic Monte Carlo simulations; hole system size and scaled as similar to n(4). We predict that disordered [n]CPPs exhibit hole mobilities increased with as high as 2 cm(2)/(V.s). Our computations show a strong correlation between reorganization energy and hole mobility (mu similar to lambda(-4)). Quantum mechanical calculations were performed on cofacially stacked molecular pairs for varying phenyl units and reveal that orbital delocalization is responsible for both decreasing reorganization energies and electronic couplings as n is increased.
Keywords: QUANTITATIVE PREDICTION; ELECTRON-TRANSPORT; ATOMIC CHARGES; CRYSTAL; CYCLOPARAPHENYLENES; AMBER